Conserving large populations of lions – the argument for fences has holes. (9th July 2013) - Creel, S.; Becker, M. S.; Durant, S. M.; M'Soka, J.; Matandiko, W.; Dickman, A. J.; Christianson, D.; Dröge, E.; Mweetwa, T.; Pettorelli, N.; Rosenblatt, E.; Schuette, P.; et al.
Abstract Packer et al. reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.